Laboratory and Pilot-Plant Scale Photocatalytic Degradation of Polychlorinated Biphenyls in Seawater Using CM-n-TiO2 Nanoparticles - Yasser A. Shaban; Mohamed A. El Sayed; Amr A. El Maradny; Radwan Kh. Al Farawati; Mosa I. Al Zobidi; Shahed U. M. Khan (International Journal of Photoenergy)
Photocatalytic degradation of polychlorinated biphenyls (PCBs) in seawater was successfully achieved at laboratory level with UV light and at pilot-plant scale under natural solar radiation using carbon-modified titanium oxide (CM-n-TiO2) nanoparticles. The photocatalytic performance of CM-n-TiO2 was comparatively evaluated with reference n-TiO2 under identical conditions. As a result of carbon incorporation, significant enhancement of photodegradation efficiency using CM-n-TiO2 was clearly observed. To optimize the operating parameters, the effects of catalyst loading and pH of the solution on the photodegradation rate of PCBs were investigated. The best degradation rate was obtained at pH 5 and CM-n-TiO2 loading of 0.5 g L−1. The photodegradation results fitted the Langmuir-Hinshelwood model and obeyed pseudo-first-order reaction kinetics.